Reclaiming hope : lessons learned in the Obama White House about the future of faith in America - Wear, Michael., 1988- (Nelson Books, 2017)
The former Obama administration "ambassador to America's believers" gives an inside account of living with faith in the White House and argues that Christians have a responsibility to be a hopeful and faithful presence in public life. As a young Christian in his early twenties, Michael Wear found himself deep inside the halls of power in the Obama administration as one of the youngest ever White House staffers. Throwing himself wholeheartedly into transforming hope into change, Wear experienced first-hand the highs and lows of working as a Christian in government. From the central role of Christians in achievements such as the adoption tax credit and directing the president's attention to human trafficking to the religious controversies and tensions that defined much of the president's time in office, Reclaiming Hope gives an unvarnished account of life inside the most powerful office in the world. At a time when large numbers of thoughtful Christians argue for a withdrawal from participation in public institutions, Wear uses his experience at the white-hot center of civic life to show how and why Christians must be involved in every aspect of cultural life--even if failures seem to outnumber successes--while working on behalf of the nation's common good"--